Higher levels of neutrophil percentage-to-albumin ratio predict increased mortality risk in patients with liver cirrhosis: a retrospective cohort study. Issue 2 (6th December 2022) - Du, Xiaofei; Wei, Xinhuan; Ma, Lixia; Liu, Xiaohui; Guo, Haiqing; Liu, Yali; Zhang, Jing
Abstract : Background: Recent studies indicated that the neutrophil percentage-to-albumin ratio (NPAR) was a predictor of mortality in several diseases. There has been no evidence to prove the predictive function of NPAR in patients with liver cirrhosis. Therefore, this study aimed to investigate the association between NPAR and clinical outcomes in cirrhotic patients. Methods: We retrospectively recruited hospitalized decompensated cirrhotic patients from the tertiary grade-A hospital. Patients with malignancy or severe cardiac, respiratory and kidney diseases were excluded. Demographical data, liver functions, complications and outcomes of cirrhosis were recorded. NPAR was calculated through the ratio of neutrophil percentage (%)/serum albumin concentration (g/dL) at admission to the hospital. Cox proportional hazards models were performed to evaluate the prognostic values of NPAR, and subgroup analyses were utilized to ensure stable results. Results: A total of 376 patients with decompensated liver cirrhosis at baseline were enrolled. The liver dysfunction, cirrhosis-related complications and mortality rate increased along with the tertiles of NPAR. In multivariate analysis, higher NPARs were independently associated with increased risk of mortality in patients with liver cirrhosis after adjustments for confounding factors (tertile 3 versus tertile 1: adjusted HR = 1.92; 95% CI, 1.04–3.56; P trend =  0.008) and each unit increase of NPAR implicated a 4% increase risk of mortality. Subgroup analysis demonstrated no significant interactions in most subgroups. Conclusion: Increased NPAR was independently correlated with a higher risk of mortality in patients with liver cirrhosis.